Influenza Virus Infection Induces a Narrow Antibody Response in Children but a Broad Recall Response in Adults - Meade, Philip; Kuan, Guillermina; Strohmeier, Shirin; Maier, Hannah E.; Amanat, Fatima; Balmaseda, Angel; Ito, Kimihito; Kirkpatrick, Ericka; Javier, Andres; Gresh, Lionel; Nachbagauer, Raffael; Gordon, Aubree; et al. (mBio, 2020)
It is known since Thomas Francis, Jr. published his first paper on original antigenic sin in 1960 that the first infection(s) with influenza virus leaves a special immunological imprint which shapes immune responses to future infections with antigenically related influenza virus strains. Imprinting has been implicated in both protective effects as well as blunting of the immune response to vaccines. Despite the fact that this phenomenon was already described almost 60 years ago, we have very little detailed knowledge of the characteristics and breadth of the immune response to the first exposure(s) to influenza virus in life and how this compares to later exposure as adults. Here, we investigate these immune responses in detail using an influenza virus protein microarray. While our findings are mostly descriptive in nature and based on a small sample size, they provide a strong basis for future large-scale studies to better understand imprinting effects. In contrast to influenza virus vaccination, natural infection induces long-lived and relatively broad immune responses. However, many aspects of the antibody response to natural infection are not well understood. Here, we assessed the immune response after H1N1 influenza virus infection in children and adults in a Nicaraguan household transmission study using an influenza virus protein microarray (IVPM). This technology allows us to simultaneously measure IgG and IgA antibody responses to hemagglutinins of many different virus strains and subtypes quantitatively with a high throughput. We found that children under 6 years of age responded to natural infection with a relatively narrow response that targeted mostly the hemagglutinin of the strain that caused the infection. Adults, however, have a much broader response, including a boost in antibodies to many group 1 subtype hemagglutinins. Also, a strong recall response against historic H1 hemagglutinins that share the K133 epitope with the pandemic H1N1 virus was observed. Of note, some children, while responding narrowly within H1 and group 1 hemagglutinins, induced a boost to H3 and other group 2 hemagglutinins when infected with H1N1 when they had experienced an H3N2 infection earlier in life. This is an interesting phenomenon providing evidence for immune imprinting and a significant new insight which might be leveraged in future universal influenza virus vaccine strategies. Finally, preexisting immunity to pandemic H1 hemagglutinins was significantly associated with protection from infection in both children and adults. In adults, preexisting immunity to non-H1 group 1 hemagglutinins was also significantly associated with protection from infection. IMPORTANCE It is known since Thomas Francis, Jr. published his first paper on original antigenic sin in 1960 that the first infection(s) with influenza virus leaves a special immunological imprint which shapes immune responses to future infections with antigenically related influenza virus strains. Imprinting has been implicated in both protective effects as well as blunting of the immune response to vaccines. Despite the fact that this phenomenon was already described almost 60 years ago, we have very little detailed knowledge of the characteristics and breadth of the immune response to the first exposure(s) to influenza virus in life and how this compares to later exposure as adults. Here, we investigate these immune responses in detail using an influenza virus protein microarray. While our findings are mostly descriptive in nature and based on a small sample size, they provide a strong basis for future large-scale studies to better understand imprinting effects.